Utilização de práticas e metodologias adaptativas de gerenciamento de projetos para o desenvolvimento de um programa de doutorado profissional - Azevedo, Gabriel Barroso de (2020)
Higher education institutions have used more and more project management tools to run development projects to create new professional postgraduate programs. The purpose of this research was to propose an adaptive project management model for the development of a professional doctoral course project in Business Administration, in order to fulfill the goals established by CAPES. For such, the qualitative approach was favored with the adoption of the single case study method. Semi-structured interviews were conducted with academic coordinators who are experts in the field in addition to the gathering of documents, thus using data triangulation to explore the phenomenon. The analysis of primary data and the analysis of documents from the Coordinating Agency for Advanced Training of Graduate Personnel (CAPES) served as inputs for analyzing and interpreting the results. As a result, we developed an adaptive project management model with the following characteristics: a) constant planning of activities, occurring in every cycle of interactions; b) iteration using short activities, allowing for more control of the project; c) validations performed continuously to ensure the goals proposed by CAPES are reached; and d) adaptable to change of scope during the execution phase of the project life cycle.